Effects of Azardirachta indica on Vascular Endothelial Growth Factor and Cytokines in Diabetic Deep Wound - Gautam, Manish Kumar; Gangwar, Mayank; Singh, Surya Kumar; Goel, Raj Kumar (Planta Medica, 2015)
A chronic, unhealed diabetic wound is one of the severe complications of diabetes mellitus. Azadirachta indica has been reported to have antidiabetic and antiapoptotic properties. The present work incorporates the healing potential of 50 % ethanol A. indica leaves extract against deep surgical wounds in streptozotocin-induced mild diabetic rats. A. indica leaves extract (500 mg/kg) was administered orally, once daily for ten days. Serum glucose, cholesterol, and triglycerides as well as body weight, food, and water intake, and tissue antioxidants (catalase, superoxide dismutase and reduced glutathione), free radicals (lipid peroxidation and nitric oxide), myeloperoxidase, total collagens (hydroxyproline, hexuronic acid and hexosamine), protein, vascular endothelial growth factor, and cytokines (tumor necrotic factor-α and interleukin-1β) were estimated. Histology was done for connective tissue formation and inflammatory and healing in deep granulation tissue after A. indica leaves extract treatment. Diabetic rats showed an increase in serum glucose, cholesterol, and triglycerides levels, food and water intake, and granular tissue free radicals, myeloperoxidase, and cytokines, but a decrease in body weight, total collagen, and vascular endothelial growth factor levels. A. indica leaves extract reversed the increased serum glucose, cholesterol, and triglycerides, food and water intake, and tissue free radicals, myeloperoxidase and, cytokines, but increased body weight, tissue antioxidants, total collagen, and vascular endothelial growth factor contents. The results thus indicated an improvement in wound healing by A. indica leaves extract in diabetic rats through enhanced angiogenesis mediated through the inhibition of hyperglycemia, oxidative stress, and down- and upregulation of inflammatory mediators and growth factor expression.
Keywords: Azardirachta indica; Malvaceae; HPLC; VEGF; TNF-α; IL-1β